A Low-Profile and Compact Split-Ring Antenna with Horizontally Polarized Omnidirectional Radiation - Kittima Lertsakwimarn; Chuwong Phongcharoenpanich; Takeshi Fukusako (International Journal of Antennas and Propagation)
This paper presents a low-profile and compact printed antenna having an omnidirectional radiation pattern with horizontal polarization to the ground. The proposed antenna consists of an inner small fed ring, an outer coupled split ring, and a ground plane. The overall dimension of the proposed antenna is 45 mm × 50.5 mm × 11.6 mm (0.138λ0 × 0.155λ0 × 0.036λ0). The −10-dB S11 of the antenna covers the 920-MHz RFID band, and the gain is about 1.45 dBi in the parallel direction to the ground plane. The measured results show good agreements with the simulated results. Furthermore, the reasons for the low-profile structure and the omnidirectional radiation pattern are also discussed.